2005
DOI: 10.1097/01.aog.0000167393.95817.dc
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results With Tension-Free Vaginal Tape on Mixed and Stress Urinary Incontinence

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
88
1
9

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(109 citation statements)
references
References 15 publications
11
88
1
9
Order By: Relevance
“…Another limitation of our study is the mean length of follow-up for subjective UUI symptoms. One study indicates that UUI symptoms return 4 years after TVT procedures, so with time; the bene¢ts of midurethral slings for UUI may decrease [Holmgren et al, 2005]. Future long-term studies are needed to con¢rm the long-term bene¢ts of midurethral sling surgery on UUI.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of our study is the mean length of follow-up for subjective UUI symptoms. One study indicates that UUI symptoms return 4 years after TVT procedures, so with time; the bene¢ts of midurethral slings for UUI may decrease [Holmgren et al, 2005]. Future long-term studies are needed to con¢rm the long-term bene¢ts of midurethral sling surgery on UUI.…”
Section: Discussionmentioning
confidence: 99%
“…5 A growing number of randomized controlled studies have shown the TVT procedure to have results similar to traditional Burch colposuspension. [6][7][8][9][10] However, very few data exist concerning long-term results [11][12][13] and quality of life after TVT placement, and there are concerns regarding postoperative voiding dysfunction or urgencies. [14][15][16] In this study, we present the results of a study on the long-term outcome of the TVT procedure assessed with symptoms and quality-of-life questionnaires.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical intervention for SUI has been shown to improve or resolve the symptoms of OAB in women with mixed incontinence [Chou et al, 2003;Segal et al, 2004]. Despite this, up to 40% of women will continue to experience persistent and bothersome OAB symptoms, which may increase with longer follow-up [Segal et al, 2004;Holmgren et al, 2005].…”
Section: Introductionmentioning
confidence: 99%